Pengaruh Kualitas Laporan Keuangan, Ukuran Perusahaan, dan Debt Maturity Terhadap Efisiensi Investasi - Hasan, Puti Zeina Hanifah; Rini Frima; Eka Rosalina; Reni Endang Sulastri (LP2M Politeknik Jambi, 2024)
This study aims to examine the effect of financial statement quality, company size and debt maturity on investment efficiency. This study tested multiple linear regression models, using spss tools. The population in the study were consumer non-cyclicals companies listed on the IDX 2019-2021 as many as 72 companies selected by purposive sampling so that the total sample was 142 data. The data used in this study are the company's financial statements on the IDX. Investment efficiency uses salesgrowth measurement, financial reporting quality uses accrual quality measurement, company size uses natural logarithm of total assets measurement, and debt maturity uses short-term debt ratio measurement. The results of this study prove that financial reporting quality affects investment efficiency, but company size and debt maturity do not affect investment efficiency.